2018
DOI: 10.1111/trf.14476
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion‐transmitted and community‐acquired babesiosis in New York, 2004 to 2015

Abstract: The increasing incidence of TTB correlated with increases in community-acquired babesiosis and infection of ticks with B. microti. Surveillance of ticks and community-acquired cases may aid identification of emerging areas at risk for Babesia transfusion transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 30 publications
(66 reference statements)
2
45
0
Order By: Relevance
“…We describe a marked overall increase in babesiosis cases in Massachusetts over time. This trend is consistent with recent findings from New York State . In addition to identification of this trend in public health surveillance data, a recent study among Medicare recipients indicated that the rate of babesiosis in Massachusetts elderly (45 per 100,000 population) was second only to Connecticut (46 per 100,000) as the highest in the United States .…”
Section: Discussionsupporting
confidence: 87%
“…We describe a marked overall increase in babesiosis cases in Massachusetts over time. This trend is consistent with recent findings from New York State . In addition to identification of this trend in public health surveillance data, a recent study among Medicare recipients indicated that the rate of babesiosis in Massachusetts elderly (45 per 100,000 population) was second only to Connecticut (46 per 100,000) as the highest in the United States .…”
Section: Discussionsupporting
confidence: 87%
“…It also concluded that blood donation screening for antibodies to and DNA from B. microti was associated with an absence of TTB. In addition, the frequency of donations from donors in the antibody‐negative window period and associated infectivity, as well as the expanding range of Babesia as determined by infected ticks, community‐acquired cases, and TTB cases have been recently reported …”
Section: Assessing the Risk And Risk Management Options (Rbdm Stage 4)mentioning
confidence: 99%
“…While this option lowers the cost of testing because it results in fewer units tested, the difficulty in identifying all patients at risk for severe disease is of concern; those at highest risk usually can be identified but most transfusion services prefer a uniform strategy. Ethical concern was raised with “underselecting” at‐risk patients to receive screened units.…”
Section: Evaluation Of Options a Through E (Category 1: Mitigate Tranmentioning
confidence: 99%
“…The Babesia Report, taken in conjunction with the FDA Draft Guidance, highlights the lack of consensus around which states should be treated as Babesia ‐endemic or as Babesia ‐risk states . The known map of B. microti incidence is expanding . Clinical babesiosis cases have been reported in 49 states and transfusion‐transmitted babesiosis (TTB) cases in 22 states to date .…”
Section: Babesia Rbdm Reportmentioning
confidence: 99%
“…Clinical babesiosis cases have been reported in 49 states and transfusion‐transmitted babesiosis (TTB) cases in 22 states to date . Ticks carrying B. microti have been detected in states currently considered nonendemic, such as Alabama, Arkansas, Indiana, and Mississippi, and there is a correlation between tick and human disease . The states identified in the Babesia Report and FDA Draft Guidance are different.…”
Section: Babesia Rbdm Reportmentioning
confidence: 99%